THE ROLE OF COLOR RELATIONSHIPS IN TEACHING STUDENTS TO DESCRIBE ARCHITECTURAL MONUMENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the process of improving the skills of good knowledge of color relationships in improving the quality of education provided to students of fine and applied arts. It is also based on the role of color relations in the depiction of historical architectural monuments, to instill a sense of pride in these beautiful historical architectural monuments, inherited from our ancestors, in the depiction of historical architectural monuments through colors and paints. shown.